Effects of Cobalt Chloride, a Hypoxia-Mimetic Agent, on Autophagy and Atrophy in Skeletal C2C12 Myotubes - Chen, Rui (Biomed Res Int, 2017)
BACKGROUND: Hypoxia-induced autophagy and muscle wasting occur in several environmental and pathological conditions. However, the molecular mechanisms underlying the effects of the hypoxia-mimetic agent CoCl(2) on autophagy and muscle atrophy are still unclear. METHODS: C2C12 myotubes were exposed to increasing concentrations of CoCl(2) for 24 hours. Quantitative RT-PCR, Western blotting, and transmission electron microscopy were performed to confirm autophagy occurs. Autophagy proteins were measured to understand the molecule mechanisms. We also inhibited hypoxic autophagy and examined the changes in myogenin expression, myotubes formation, and apoptosis. RESULTS: Our results showed that CoCl(2)-mimicked hypoxia upregulated the expression of the autophagy-related proteins LC3, HIF-1α, BNIP3, p-AMPKα, and beclin-1, whereas p62 and p-mTOR were downregulated. In addition, the autophagosome could be observed after CoCl(2) induction. The expression of the autophagy-related E3 ligase parkin and the muscle-specific ubiquitin ligase atrogin-1 was increased by CoCl(2). Inhibition of autophagy by 3MA increased myogenin expression and promoted myotubes formation and the percentage of cell death was decreased. CONCLUSIONS: Our results confirmed that CoCl(2)-mimicked hypoxia induced autophagy via the HIF-1α/BNIP3/beclin-1 and AMPK/mTOR pathways. Our results also revealed an important link between autophagy and muscle atrophy under hypoxia, which may help to develop new therapeutic strategies for muscle diseases.